Niche-proxies of Hydrocarbon-impacted Rhizosphere Soil of Weeds of Bodo in Gokana, Rivers State, Nigeria - , E. Effiong; , O. K. Agwa; , G. O. Abu (Archives of Current Research International, 2020)
Niche-ecology and isolation studies of microbes from the environment have been described as the bedrock and driving-force for bioprocess industry. This investigation was designed to determine the microbiological quality of weeds growing on aged-crude oil polluted soil. Ten (10) weeds Cyperus esculentus, Scleria pauciflora. Asystasia gangetica Harungana madagascariensis, Ancistoclaudus tectorius, Kyllinga erecta, Cinna arundinacea, Brassica chinensis, Cyperus difformis, Kyllinga bulbosa and Brachiaria mutica and their rhizospheric soil were obtained from Bodo, Gokana LGA, Sludge farm and Botanical garden of the University of Port Harcourt, Rivers State, Nigeria. The soil was enriched in Mineral Salt Media and Bonny Light Crude Oil, prior to the spread-plating on solidified media. Result of the analysis showed pH of soil samples ranged from 5.26-7.2; Electrical conductivity was 53.4-80.31µS/cm, and phosphate 0.74-5.35 mg/kg. Levels of Vanadium in pre-impacted rhizosoil obtained from Kyllinga erecta and Cinna arundinaceae were 0.61 and 0.70 mg/kg respectively. Moisture content of soil obtained from polluted and pristine environments were 11.75% and 17.82% respectively. Permeability indices were 9.0 describing the pristine soil to have low plasticity. Total heterotrophic bacterial count was within 3.5-8.0 Log10 Cfu/g distributed among the weed rhizospheres. Cyperus esculentus rhizosphere soil was more dominated with others like Achromobacter sp, B. lichenformis, B. anthracis, B. subtilis, B. fumari, Arthrobacter sp, Pseudomonas sp, P. aeruginosa, P. fluorescens. Fungal isolates were Aspergillus terreus, Trichoderma sp, and Fusarium sp. These findings further support the rhizosphere of plants as a rich bioresource for biomining of high throughput strains for biotechnological application.